EVALUATION OF HEPATITIS C VIRUS GENOTYPING PROTOCOLS FOR USE IN A DIAGNOSTIC SETTING - Isaac Thom Shawa; Hopkins, Mark (International Journal of Medical Research, 2013)
Background: Hepatitis C virus (HCV) has been reported to be the most common cause of chronic viral Hepatitis with increased prevalence rate worldwide. HCV genotype is an important predictive factor in the outcome of HCV treatment, therefore an essential component of clinical practice. Molecular methods are the most common diagnostic tools for HCV genotyping. HCV genotype might also have relevance for newer antiviral therapies in development. Objectives: To develop and evaluate new cost-effective molecular methods for HCV genotyping using analytical instruments which were in place at Royal Liverpool University Hospital (RLUH) and to assess their sensitivity and specificity. Methods: The plasma or serum RNA purification was done by automated QIAsymphony and QIAcube equipment. PCR assays capable of detecting and distinguishing HCV genotype by nucleotide probe or melt analysis were compared. The two-step PCR and one-step real-time PCR methods were assessed. The NS5B PCR was used to amplify the 5’NTR region of HCV for sequencing using Qiagen RT-PCT kit. The method was evaluated using HCV genomic sequence data as the gold standard. Results: In preliminary PCR assessments, two-step real-time PCR amplified the products but could not be continued as efforts were made to assess and improve the one-step RT-PCR method for diagnostic purposes. Out a total of 71 samples 65 gave definitive genotype results, 59 were concordant and 6 mismatched. The discordant samples were repeated to confirm the genotypes but the results were similar. 6 samples could not be amplified. A Kappa value of 0.869 (p<0.001) indicating a 90.8 percent agreement was obtained. The sensitivity and specificity were 91.5% and 100% respectively. Conclusions: The PCR amplification of NS5B HCV regions showed that the method is capable of detecting HCV genotypes, however it is unable to discriminate mixed genotypes. Whereas real-time PCR method is capable of detecting mixed genotypes, the genotype call may be less reliable. On the other hand, the sequencing method used in this study has an inherent limitation of giving definitive genotypes one at a time. Further efforts should be made to develop the real-time PCR to detect mixed genotypes.